Noninvasive Follicular Thyroid Neoplasm with Papillary-Like Nuclear Features: An Evidence-Based Nomenclature Change. (9th February 2017) - Jug, Rachel; Jiang, Xiaoyin
Abstract : A consensus panel recently used clinical evidence and pathologic parameters to rename noninvasive encapsulated follicular variant of papillary thyroid carcinoma to noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) to better reflect the indolent course of this tumor. NIFTP has stringent histopathologic diagnostic criteria established by the panel, including papillary-like nuclear features, and submission of the entire tumor capsule to exclude invasion. From a molecular standpoint, NIFTP is often characterized by RAS-type mutations, similar to other follicular-patterned lesions. While there has been prior evidence in the literature for the low malignant potential of these tumors, projects moving forward will help to independently reinforce the reliability of these criteria and nomenclature. With planned inclusion of NIFTP into the latest World Health Organization endocrine tumor classification scheme, this nomenclature shift provides a model for pathology efforts to refine diagnostic classifications to better guide treatment. In this review we discuss this nomenclature change and review the current literature.